Trainers’ characteristics affecting online training effectiveness: a pre-experiment among students in a Malaysian Secondary School - Abdul Aziz, Siti Fardaniah; Hussein, Norashikin; Husin, Nor Azilah; Ibrahim, Muhamad Ariff (MDPI, 2022)
Abstract: The COVID-19 pandemic has highlighted the implementation of the Fourth Industrial Revolution (4IR), especially in the educational system, in which online learning can also be used as online training among school students. Interestingly, prior studies have highlighted trainers’ role as the most important factor affecting online training. However, prior studies that reported the effectiveness of online training among school students and the right trainers’ characteristics to sustain its effectiveness have been very limited. Therefore, the objective of this study was to determine online training effectiveness among 150 students in a Malaysian high school using pre- experimental research. Trainers’ characteristics perceived by participants were also determined and compared between classroom and online training. Findings indicated that online training was significantly effective regardless of gender and race differences; trainers’ characteristics explained 40.5% of variance in online training effectiveness. However, the school students preferred classroom training compared to online training; trainers’ characteristics were better in classroom training. Hence, it can be concluded that online training among school students can be effective; however, the characteristics of trainers can be improved to sustain the effectiveness of online training. These results have implications for the sustainability of effective 4IR in the educational system for the post-pandemic era.